Four-Component Reaction of Trialkyl Phosphites, Amines, and Electron-Deficient Acetylenic Compounds: Synthesis of Phosphonate Derivatives in Water - Hossaini, Zinatossadat; Rostami-Charati, Faramarz; Ghasemian, Mahboubeh; Abad, Saeid Afshari Sharif (Synlett, 2015)
An effective route for the synthesis of phosphonate derivatives is described. This procedure involves the reaction of a trialkyl phosphites and dialkyl acetylenedicarboxylate in the presence of amines in water as the solvent at room temperature.
Keywords: water; primary amines; trialkyl phosphites; four-component reactions; dialkyl acetylenedicarboxylate